Customer Satisfaction: A Game-Changer in Seller's Adverse Selection - Kina, Nurul Fitri Rizkina; Yanthi, Merlyana Dwinda; Aini Haron, Nur Quratun (International Economic Conference of Business and Accounting, 2024)
Indonesia has potential for social commerce to grow, GMV was estimated US$25 million last year. However, customers are experiencing passive and active opportunistic behavior among sellers which ultimately leads to higher seller uncertainty in social commerce than in e-commerce. Adverse selection occurs through pre-purchase uncertainty. Since satisfied customers are more likely to become loyal customers, customer satisfaction is an important performance indicator of a company's effectiveness. Therefore, this study attempts to bridge this gap by investigating the influence of customer satisfaction on seller’s adverse selection. A self-administered structured questionnaire was used for data collection. The empirical evidence from 126 Tik Tok shop customers shows that the customer satisfaction indicators, positive review comments and seller’s services has a negative influence on seller’s adverse selection. Meanwhile, the seller’s popularity has not influence on seller’s adverse selection